From Newsroom to Metaverse: Media Human Resource Transformation and Organizational Communication among Generation Z - Rizky Muharram; Afwan Syahril Manurung; Syifa Urrahmah; Yoserizal Saragih; Zanniro Sururi Hsb (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
This study aims to analyze the transformation of human resource (HR) management in the media industry, which is now dominated by Generation Z, a digital-native generation that brings new values, behaviors, and expectations to work systems. Amidst the acceleration of digitalization and the emergence of technologies such as the metaverse, augmented reality, and artificial intelligence, HR management in newsrooms is required to adapt not only technologically but also culturally. This study uses a qualitative approach with descriptive methods, supported by in-depth interviews and observations with ten informants from the Gen Z group working in the digital media sector. The results show that Gen Z is not only an implementer but also an agent of change that drives a shift in work paradigms: from bureaucratic structures to collaborative systems, from administrative control to a values-based approach. Gen Z demands work flexibility, space for participation, and a management system that values ​​diversity, transparency, and sustainability. By combining Kurt Lewin's Change Management theory with John Kotter's approach, this study finds that most media organizations are still in the "unfreeze" stage and have not yet optimally built work systems that are truly aligned with the characteristics of Gen Z. The transformations that have occurred so far tend to be technical and partial, not addressing comprehensive structural and cultural changes. This study recommends that media companies undertake a strategic reorientation of human resource management as a foundation for industry sustainability in the digital and metaverse era.